First-principles calculations in real-space formalism : electronic configurations and transport properties of nanostructures - Hirose, Kikuji (Imperial College Press, 2005)
With cutting-edge materials and minute electronic devices being produced by the latest nanoscale fabrication technology, it is essential for scientists and engineers to rely on first-principles (ab initio) calculation methods to fully understand the electronic configurations and transport properties of nanostructures. It is now imperative to introduce practical and tractable calculation methods that accurately describe the physics in nanostructures suspended between electrodes. This timely volume addresses novel methods for calculating electronic transport properties using real-space fo.